Radiation-induced sarcomas: A single referral cancer center experience and literature review - Laurino, Simona; Omer, Ludmila Carmen; Albano, Francesco; Marino, Graziella; Bianculli, Antonella; Solazzo, Angela Pia; Sgambato, Alessandro; Falco, Geppino; Russi, Sabino; Bochicchio, Anna Maria (Frontiers in Oncology, 2022)
Background and Objective: The oncologic risk of ionizing radiation is widely known. Sarcomas developing after radiation therapy (RT) as “iatrogenic disease of success” have been reported, and they are a growing problem because advancements in cancer management and screening have increased the number of long-term survivors. Although many patients have undergone to radiation treatment, only few data are available on Radiation-Induced Sarcomas (RIS). Methods: We examined the medical and radiological records of 186 patients with immunohistochemistry proven Soft Tissue and Bone Sarcomas referred to IRCCS CROB Centro di Riferimento Oncologico della Basilicata from January 2009 to May 2022. Among them, seven patients had a histologic diagnose of secondary RIS, according to Cahan’s criteria. Clinicopathological features and treatment follow-up data of the seven patients with RIS were analyzed retrospectively. Results: Among these secondary RIS, 5 arose in irradiated breast cancers (5/2570, 0.19%) and 2 in irradiated head and neck cancers (2/1986, 0.10%), with a mean onset latency time of 7.3 years. The histology of RIS were: 1 desmoid tumor cervical localized, 2 angiosarcoma, 1 chondrosarcoma, 2 leiomyosarcoma, 1 undifferentiated pleomorphic sarcoma. Out of the 7 RIS, 1 received radiotherapy, 1 had electrochemotherapy (ECT), 1 received a second-line chemotherapy, 3 had three lines of chemotherapy, 1 had radiofrequency ablation, chemotherapy and ECT. Median survival time is 36 months. No significant survival differences were found stratifying patients for age at RT, latency time, and age at RIS occurrence. Conclusions: Radiation-induced sarcoma represents a possible complication of long-survivor cancer patients. Therefore, the adhesion to a strict follow-up after the radiation treatment is recommendable to allow early diagnosis and best manage RIS patient. After the planned follow-up period, considering the long-term risk to develop a RIS, a specific multispecialty survivorship care plan could be of benefit for patients.